Analysis of parametric and time-angle methods for determining the distance and positioning of unmanned aerial vehicles - Сербул, Олександр; Ярмоленко, Володимир; Ізовіта, Олесь (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The paper considers modern approaches to determining the distance and positioning of unmanned aerial vehicles (UAVs) using radio signal parameters—RSSI, SNR, LQ—as well as ToF, TDoA, and AoA methods. The relevance of the research in the context of digital transformation and limitations of satellite technologies (GPS/GNSS) is justified. The accuracy, advantages, and disadvantages of each method are analyzed, and an integrated formula for distance estimation based on a combination of RSSI+SNR+LQ is presented. It is shown that the combination of parametric and time-angle methods increases the reliability and accuracy of UAV navigation. The prospects for the development of hybrid positioning systems using self-calibration algorithms, Kalman filters, and integration with 5G/6G and IoT technologies are noted. У роботі розглянуто сучасні підходи до визначення відстані та позиціювання безпілотних літальних апаратів (БПЛА) за допомогою параметрів радіосигналу — RSSI, SNR, LQ, а також методів ToF, TDoA та AoA. Обґрунтовано актуальність дослідження в умовах цифрової трансформації та обмежень супутникових технологій (GPS/GNSS). Проаналізовано точність, переваги та недоліки кожного з методів, наведено інтегровану формулу оцінки відстані на основі комбінації RSSI+SNR+LQ. Показано, що поєднання параметричних і часово-кутових методів підвищує надійність і точність навігації БПЛА. Зазначено перспективи розвитку гібридних систем позиціонування з використанням алгоритмів самокалібрування, фільтрів Калмана та інтеграції з технологіями 5G/6G та IoT.